Reconfiguring connected resource distribution systems - Rosendall, P.; Pekala, M.; Scheidt, D. (Computational Intelligence in Control and Automation (CICA), 2011)
In this paper we consider complex mechanical systems that operate within harsh, uncertain environments where mission success depends critically upon the system's ability to monitor and maintain its own internal health. In particular, we focus on the problem of reconfiguring a system's internal resource distribution subsystems in response to one or more damage events. We present a graph-based approach that guarantees the resulting states adhere to a desirable resource segregation constraint. We also provide results using this approach in conjunction with optimization techniques to reconfigure a representative hardware test platform.